Teori dan Model Pengembangan Sumber Daya Manusia di Lembaga Pendidikan Islam Menurut Ahmad Fatsh Yadin - Rini Setyaningsih (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2021)
This study discusses the theory and model of human resource development in islamic education in Ahmad Fatah Yasin's view. The purpose of this research is to find out about the theories and models used in human resource development. This research is a Library Research (library research) using inductive analysis techniques. In the concept of human resource development Ahmad Fatah Yasin explains theories regarding human resource development, of which there are two approaches to developing the quality of Human Resources (HRM), namely the first